Solar water splitting: preserving the beneficial small feature size in porous α-Fe2O3 photoelectrodes during annealing - Wang, Lei; Lee, Chong-Yong; Schmuki, Patrik (Journal of Materials Chemistry A, 2012)
We prepared mesoporous extgreeka-Fe2O3/FTO electrodes by a simple anodic precipitation and annealing method. The classic problem is that when annealed in air at >500 °C, the individual particle size increases from ≈20 nm to 40–60 nm. This grain growth is highly detrimental for the water splitting efficiency. In the present work we show that grain coarsening can efficiently be prevented by a two-step annealing method in Ar, leading to photocurrent densities for such electrodes (obtained in 1 M KOH solution) of up to 2.6 mA cm-2 at 1.6 V vs. RHE under AM 1.5 100 mW cm-2 illumination, which is significantly higher than 1.5 mA cm-2 for conventionally annealed samples.
EAM Import::2019-03-13